Pengetahuan dan sikap remaja tentang protokol kesehatan di masa new normal - Putu Noviana Sagitarini; Ni Komang Tri Agustini (Holistik Jurnal Kesehatan, 2022)
Background: On March 11, 2020, the World Health Organization (WHO) declared Covid-19 a worldwide pandemic. The number of Covid-19 cases worldwide is increasing every day. The Indonesian government uses the terms Restrictions on Community Activities and Large-Scale Social Restrictions to decrease Covid-19 cases. However, since early June 2020, the Government of Indonesia has begun to relax Restrictions on Community Activities and Scaled Social Restrictions and hopes that people will adopt new habits, better known as the new normal. The application of health protocols to break the chain of the spread of Covid-19, especially in adolescents, requires good understanding and knowledge so that adolescents can have a positive attitude towards health protocols in order to reduce the transmission of Covid-19.Purpose: Knowing that there is a relationship between knowledge and adolescent attitudes about health protocols in the new normal.Method: This study uses a descriptive correlation design through a cross-sectional approach. The sampling method is probability sampling with simple random sampling. The number of research samples was 191 respondents. The data collection tool used is a questionnaire. Data were analyzed using univariate analysis and bivariate analysis with the Spearman Rho test.Results: The results of the analysis showed that most of the respondents had knowledge in a good category, namely 56%, and as many as 52.9% of respondents had attitudes in a good category about health protocols in the new normal period. Bivariate analysis showed that there was a relationship between knowledge and adolescent attitudes about health protocols in the new normal period with p-value < 0.001 and r value = 0.730, which means the strength of the relationship is in a strong category.Conclusion: There is a positive relationship between knowledge and adolescent attitudes about health protocols in the new normal at SMK PGRI 3 Denpasar.Keywords: Knowledge; Attitude; Adolescent; Health Protocol; New Normal; post-COVID-19 eraPendahuluan: Pada tanggal 11 Maret 2020, World Health Organisation (WHO) menyatakan bahwa Covid-19 sebagai penyakit pandemi di seluruh dunia. Jumlah kasus Covid-19 di seluruh dunia setiap harinya mengalami peningkatan. Pemerintah Indonesia menggunakan istilah Pembatasan Kegiatan Masyarakat dan Pembatasan Sosial Berskala Besar  untuk mengurangi peningkatan kasus Covid-19. Namun sejak awal Juni 2020, Pemerintah Indonesia mulai melonggarkan Pembatasan Kegiatan Masyarakat dan Pembatasan Sosial Berskala dan berharap masyarakat mengadopsi kebiasaan baru yang lebih dikenal dengan new normal. Penerapan   protokol   kesehatan guna pemutusan  mata  rantai  penyebaran  Covid-19 terutama  pada  remaja  memerlukan pemahaman  dan  pengetahuan  yang  baik sehingga remaja bisa bersikap yang positif terhadap protokol kesehatan guna mengurangi penularan Covid-19.Tujuan: Mengetahui  ada hubungan antara pengetahuan dengan sikap remaja tentang protocol kesehatan di masa new normal.Metode: Penelitian ini menggunakan desain deskriptif korelasi melalui pendekatan cross-sectional. Cara pengambilan sampel dengan probability sampling dengan simple random sampling. Jumlah sampel penelitian sebanyak 191 responden. Alat pengumpulan data yang digunakan adalah kuesioner. Data dianalisis menggunakan analisis univariat dan analisis bivariat dengan uji Spearman Rho.Hasil: Hasil analisis didapatkan sebagian besar responden memiliki pengetahuan dengan kategori baik yaitu 56%, sebanyak 52,9% responden memiliki sikap dengan kategori baik tentang protokol kesehatan di masa new normal. Analisis bivariat menunjukkan bahwa ada hubungan antara pengetahuan dengan sikap remaja tentang protokol kesehatan di masa new normal dengan p value< 0,001 dan nilai r  = 0,730 yang artinya kekuatan hubungannya termasuk kategori kuat.Simpulan: Terdapat hubungan positif antara pengetahuan dengan sikap remaja tentang protocol kesehatan di masa new normal di SMK PGRI 3 Denpasar.